Caracterização e modelagem dos processos erosivos com interface canal-encosta em bacias de elevado gradiente topográfico: o caso da bacia experimental do rio Guarda Mor - Bernardi, Felipe (2022)
Water erosion is closely related to environmental preservation, sanitary quality and general infrastructure problems. The phenomenon of sediment transport in channels is extremely complex because it is a non-punctual phenomenon, resulting from factors such as sediment availability, flow energy and physical characteristics of the fluvial environment. The integration of erosion phenomena interpretation can be established through process modeling. However, the use of mathematical models requires representativeness of the natural environment by parameters and reliability between prediction and observation performed by hydrological monitoring techniques. Thus, this work objective is quantifying the erosion phenomena at the hydrographic basin scale and its river transport through monitoring techniques that allow evaluating the prediction and interpretation capacity of mathematical models of simulation of erosive processes of hillslope and channel. The study region comprises the watershed of the Guarda Mor river, characterized by mountainous relief, fragile soils, and a gravel bed river. Monitoring was carried out by monitoring precipitation events and directed towards measuring liquid and solid rates (suspension and bedload) for an outlet with a drainage area of 18.5 km². The guideline of the analysis is to formalize a set of modeling techniques for simulating erosion at the watershed and channel scale to assess the impact of increased precipitation caused by climate scenarios. The calibration of the LISEM model with observed data from the monitoring of hydrological and erosion variables allowed defining a set of parameter values for hydrological and erosion simulation and performing the simulation of scenarios in the hydrographic basin. The HEC-RAS 2D model has difficulties in simulating the hydraulically rough environment of a gravel bed channel. The HEC-RAS 2D model best represented river erosion using the Yang transport equation and the Parker exposure and protection function. The choice of the protection and exposure function had a greater impact on the representation of river erosion than the choice of the transport capacity equation. The combination of the evaluated LISEM and HEC-RAS models with field observations allowed the simulation of erosion impacts of different climatic scenarios in the watershed and in the drainage channel.